Bone meal, wood ash and fish waste fertilizer for tomato plant - Hashim, Shazana; Mohd Sap, Nur Asyikin; Mohamad Hanafiah, Noor Mursyidah; Vasu, Ashwinii (Penerbit UTHM, 2020)
Based on Utusan Online 24 March 2017, consuming vegetables and fruits that are fertilized by chemical fertilizers and the use of insecticides are now a global threat (Utusan, 2017). One way of avoiding such a threat is by producing organic fertilizers from kitchen scraps and crops residues. Organic fertilizer is derived from biodegradable matter such as plant waste, animal waste or powdered mineral (Julie, 2016). The production of organic fertilizer is to reduce the usage of chemical fertilizer that significantly reduces pollution on earth. Organic fertilizer contains nutrients in its most pure form where it is minimally processed and allows both the plant and the soil to be healthy and strong (Julie, 2016). As the organic fertilizer breaks down, they improve the structure of the soil and increase their ability to hold water and the nutrients. In order to break down and release nutrients into the soil, microorganisms are needed and these microorganisms need warmth and moisture to carry out their task.